Prevalence and barriers to early initiation of breastfeeding among urban poor full-time readymade garments working mothers: a mixed-methods study in Bangladesh - Md. Rabiul Islam; Tasnim Tamanna; Nusrat Azrin Mohsin; Arifa Farzana Tanha; Nusrat Hossain Sheba; JMA Hannan (BMC, 2024)
Abstract Background Early initiation of breastfeeding is the initiation of breastfeeding within one hour of birth, which plays a significant role in a born baby's growth and survival, however its prevalence and predictors among urban full-time readymade garments (RMG) working mothers are not investigated. The purpose of this study is to determine the prevalence and factors affecting early initiation of breastfeeding among urban RMG working mothers. Methods A sequential explanatory mixed-methods study was conducted between March 2023 and December 2023 in Dhaka, Bangladesh. A total of 452 full-time female RMG workers were included for the quantitative study. Qualitative study was carried out among 30 full-time female RMG workers, four female physicians who were employed in the RMGs, four RMG factory managers, and four local pediatricians. Results The prevalence of early initiation of breastfeeding was 40% among the women. It was significantly associated with various factors, including socio-cultural barriers, the advanced age of the mother (AOR 3.93, 95%CI 1.18, 13.04), lack of education (AOR 6.86, 95%CI 1.11, 42.49), lack of awareness, and cultural practices such as initiating goat milk and honey instead of breast milk. The absence of colostrum feeding (AOR 8.96, 95%CI 4.30, 18.70) and pre-lacteal feeding (AOR 0.06, 95%CI 0.03, 0.11) were significant baby feeding practice-related barriers to early initiation of breastfeeding. Maternal health factors, notably post-delivery sickness, cesarean delivery, and lack of breastmilk production, were revealed as a significant hindrance to the early initiation of breastfeeding explored from qualitative analysis. In addition, RMG factory-related factors that significantly affect early initiation of breastfeeding include a strong focus on production, a busy schedule, and a lack of initiative regarding the early initiation of breastfeeding. Conclusions The prevalence of early initiation of breastfeeding among RMG working women is poor. This study emphasizes the need for interventions that address specific challenges of early initiation of breastfeeding faced by working mothers in RMG sectors, including improved lactation education, increased awareness to mitigate cultural barriers, RMG factory-based initiatives to empower female workers early initiation of breastfeeding, and preparing early initiation of breastfeeding -friendly post-cesarean unit at the health care facility.